Penerapan Metode MPE dalam Penilaian Kinerja Penyuluh Pertanian UPT BPP Sukaraja - Suranti, Dewi; Sari, Herlina Latipa (UNIVED Press, 2018)
In order to build qualified and reliable agricultural human resources, it is necessary for professional, creative, innovative and global oriented Agricultural Extension workers in the provision of productive, effective and efficient extension services. Agricultural Extension is directed to carry out advisory and consultation tasks for the main actors and business actors in developing their agribusiness business, so the adoption of appropriate technology can run well and in turn increase the empowerment of the main actors, productions, productivity, income and welfare of farmers and their families. The performance of agricultural extension workers can be seen in the aspects of preparation, implementation, evaluation and reporting, development of agricultural extension and agricultural extension profession profession. In addition, agricultural extension programs should be based on analysis of farmers' needs and reflect current target audience conditions. Exponential Comparison Method in appraisal of farmer extension performance at UPT BPP Sukaraja aims to know the performance of agricultural extension in conducting counseling at UPT BPP Sukaraja. This is due to the lack of extension workers in BP3K Sukaraja. The results of the resulting assessment in the form of work performance ranking of each extension worker. Based on the result of the calculation methods show performance rankings. With this is expected to make it easy for UPT BPP sukaraja in carrying out routine performance appraisal performance of extension workers who had been a constraint in conducting appraisal performance extension. Agricultural extension workers can carry out their duties and responsibilities